Descolamento prematuro da placenta: revisão integrativa da literatura - Alves, Camila Fátima (Universidade do Vale do Rio dos Sinos, 2016)
The placental abruption (DPP) is regarded as an obstetric emergency with high potential for maternal and fetal morbidity and mortality. Objective: To identify the scientific literature productions on the theme dealing with the DPP. Method: This is an integrative literature review. We opted for the query to databases Latin American and Caribbean Health Sciences (LILACS) and Scientific Electronic Library Online (SciELO), between 2005 and 2015, considering only the national scientific production. For this, we used a summary table as a tool for data collection and subsequent analysis, which completed the following: product name, authors, place of origin of the scientific production, the study objectives, results and considerations / conclusions . Results: The journal that showed the highest number of publications was the Medical Journal of Minas Gerais, with 60% of the records. Early diagnosis and the implementation of appropriate obstetric conduct the admission of pregnant women to health services are essential to good maternal / fetal prognosis. Conclusion: It is suggested that new studies relevant to the topic in question are promoted, with emphasis on nursing care and its impact on maternal / fetal outcomes.
Keywords: Descolamento prematuro da placenta; Gravidez de alto risco; Cesárea; Placental abruption; Caesarean section; High-risk pregnancy